Evaluating the Technical Feasibility of Retention Basins for Flood Control in Palembang City - Febrinasti Alia; Muhammad Baitullah Al Amin; Bimo Brata Aditya; Citra Indriyati (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2019)
Flood control is one of the prevention methods which involves various engineering sciences and is unique. One of structural flood control methods is retention basin with the goal of containing a certain storm event flow volume and obtaining a specific peak flow reduction. This paper’s objective is to describe how to assess the performance of retention basin physical components quantitatively on seven retention basins in Palembang City. The reference and the parameter used in this research are referred to Drainage Systems Assessment Design (Vadlon, 2011) that is based on Standard Procedure of Retention Basins and Polders Construction according to Public Works Ministry of Cipta Karya Directorate General and the Regulation of Public Work Ministry No.32/PRT/M/2007. The result of the assessment is that there are three retention basins which are in good condition, namely Kambang Iwak Besak (63,9%), Simpang Polda (60,34%), and Kambang Iwak Kecil (56,8%); meanwhile the other four basins are in bad conditions, namely RS. Siti Khodijah (43,01%), Palembang Icon (41,93%), Kemang Manis (7,03%), and Brimob (0,94%). Therefore, the assessment of the retention basins towards its effectiveness on flood controlling and handling priority level is done by hydraulic modeling simulations and GIS. 4. Based on the inundation priority assessment of simulated flood depth and duration, it can be inferred that the retention basin of Kambang Iwak Besak, Kambang Iwak Kecik, Palembang Icon, RS Siti Khodijah, and Kemang Manis have low priority handling level. Meanwhile, Brimob and Simpang Polda retention basins have high priority handling level.